Food and Alcohol Disturbance (FAD) in the U.S. and France: Nationality and gender effects and relations to drive for thinness and alcohol use. (December 2018) - Choquette, Emily M.; Ordaz, D. Luis; Melioli, Tiffany; Delage, Beatrice; Chabrol, Henri; Rodgers, Rachel; Thompson, J. Kevin
Abstract: Objective: Food and Alcohol Disturbance (FAD), colloquially coined "drunkorexia, " is a set of behaviors that encompasses restriction of calories, over-exercise, and other compensatory behaviors before, during, or after alcohol use to offset caloric intake or maximize intoxication. To date, this phenomenon has not been compared in a cross-cultural sample. Method: The Compensatory Eating and Behaviors Related to Alcohol Consumption Scale (CEBRACS), Eating Disorder Inventory – Drive for Thinness Subscale (EDI-DT) and Alcohol Use Disorders Identification Test of Consumption (AUDIT-C) were completed by 502 American (73% female) and 365 French (68% female) college students. Results: Just over half (56.70%) of French and American (55.83%) participants engaged in FAD. Nationality was found to be a significant moderator of the relationship between alcohol use and FAD for both compensatory ( p  = .013) and intoxication ( p  = .01) purposes, such that Americans who drank more engaged in more FAD. Further, nationality moderated the relationship between drive for thinness and FAD for compensatory purposes ( p  = .005), but not for intoxication purposes ( p  = .10). At higher levels of drive for thinness French participants were more likely to engage in FAD for compenatory purposes. Discussion: There is growing concern around how maladaptive eating and drinking behaviors intersect within the college population. These findings suggest that FAD is present cross-culturally, but that the relationships between predictors vary across culture. Thus, culture should be taken into consideration in the development of interventions for FAD. Highlights: There were significant cross-cultural differences in FAD. Just over half of French and American participants engaged in FAD. Nationality moderated the relationship between alcohol use and FAD. Nationality moderated the relationship between drive for thinness and FAD.